Identification of Gas Products from Pyrolysis Process of Waxes Used in Lost-Wax Casting Technology - Żymankowska-Kumon, Sylwia; Kolczyk-Tylka, Joanna (Journal of Casting & Materials Engineering, 2018)
Foundry waxes currently used in lost-wax casting technology are composed of paraffin, stearin, and – to a lesser extent – ceresin, polyethylene wax, and other natural and synthetic waxes. Most of these compounds are non-toxic; however, they may release aromatic hydrocarbons as a result of exposure to high temperatures. Based on a chromatographic analysis (pyrolysis gas chromatography-mass spectrometry, Py-GC/MS), the compounds that are separated from the popular wax mixtures used in foundries were evaluated (as well as the impact they may have on foundry workers). For this purpose, the three main stages of the process (wax, burnout, and pouring) were analyzed, and the appropriate test temperature was chosen (similar to the actual conditions during the process).